Defeating Buffer Overflow: A Trivial but Dangerous Bug - Black, Paul E.; Bojanova, Irena (IT professional, 2016)
With the C programming language comes buffer overflows. Because it is unlikely that the use of C will stop any time soon, the authors present some ways to deal with buffer overflows--both how to detect and prevent them.